QASAM DALAM AL-QUR’AN (SUATU TINJAUAN USLUB NAHWIYYAH) - Amir, Amir (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
Qasam is one of Arab’s habitation to communicate and  for making sure with the others. Because that, al-Qur’an Comes to Arab’s surrounding  and also in Arabic language, so that Allah swt. Use the  Qasam to celebrate and socialization His Kalam or al-Qur’an. In this research consists of two  problems, the first how the substance of the Qasam in the al-Qur’an, the second how the style of Qasam inArabic or Nahwu In order to solve these problems, the researcher collected data from many sources needed.This research the writer use qualitative research, and also include the data through the library research.